(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article deals with the scientific heritage of V.I. Shapovalov. His views on the problem of adequacy and equivalence of translations of Kyrgyz oral epic poetry into Russian. The history of translation studies from the 30s to 50s of the XX century and its main distinctive characteristics, concepts, and approaches are traced. Special attention is paid to the problems of literalism and free translation, as well as to indirect translation (translation according to the liner notes), which became predominant in this period. The author substantiates the idea that translations made by translators without knowledge of the original language do not fulfil translation norms, and thus do not fulfil their main task – to convey the content of an epic work in all its variety of aesthetic characteristics. The author gives a generalized characteristic of scientific-folkloristic translations embodied in the series “Epic of the Peoples of the USSR” and “Folklore Monuments of the Peoples of Siberia and the Far East”